2018
DOI: 10.11598/btb.2019.26.1.989
|View full text |Cite
|
Sign up to set email alerts
|

Agrobacterium-MEDIATED GENETIC TRANSFORMATION OF SEAWEED Kappaphycus alvarezii USING Gα GENE AND CALLUS CULTURES

Abstract: Cottonii seaweed (Kappaphycus alvarezii Doty) is one of the most important commercial sources of carrageenans which are widely used in the pharmaceuticals and food industries. A problem in the cultivation of this seaweed is the ice-ice disease, which is caused by extreme changes in environmental conditions such as temperature and seawater salinity. Gene transformation to produce Cottonii seaweed transgenics that are tolerant to environmental stress is a potential solution to this problem. Gα gene encodes for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The differences in genetic diversity of strains belonging to K. alvarezii may be one of the causes. [12] have done genetic engineering in K. alvarezii for ice-ice disease controls using the Gα gene extracted from soybean into the callus of K. alvarezii using Agrobacterium tumefaciens and regenerated modified callus cells to transgenic plantlets. Results revealed that K. alvarezii transgenic plantlets with Gα genes were successfully created.…”
Section: Ice-ice Diseasementioning
confidence: 99%
“…The differences in genetic diversity of strains belonging to K. alvarezii may be one of the causes. [12] have done genetic engineering in K. alvarezii for ice-ice disease controls using the Gα gene extracted from soybean into the callus of K. alvarezii using Agrobacterium tumefaciens and regenerated modified callus cells to transgenic plantlets. Results revealed that K. alvarezii transgenic plantlets with Gα genes were successfully created.…”
Section: Ice-ice Diseasementioning
confidence: 99%